The role of the large-scale modes of climate variability in the Southern African wave climate - Oliver, Benjamin (Department of Oceanography, 2022)
The wave energy flux along the southern African coastline regularly reaches extreme levels, seriously impacting coastal communities, infrastructure, as well as near-coast and offshore marine operations. Understanding the drivers behind past high wave energy events and their frequency is key to forecasting future events. Using both the in-situ wave buoy data recorded by the Council for Scientific and Industrial Research (CSIR) and satellite altimeter data, 2 global wave hindcast products are evaluated and the best-performing is chosen to assess long-term variability and trends around the coastline between 1979 and 2020. Seasonal trend analysis revealed significant increasing trends in offshore flux for all seasons, with spring having the strongest coastal trends. The role of the Southern Annular Mode (SAM), El Nino Southern Oscillation (ENSO), and the semi-annual oscillation (SAO) on the interannual monthly wave energy flux and direction variations were assessed. Individually each mode showed significant anomalies for at least one season, however often there are multiple active modes making things more complex. SAM has the strongest control on the flux anomalies with the negative (positive) SAM associated with above (below) average anomalies in both flux and westerly (easterly) direction anomalies. ENSO directly impacts the summer wave climate, and the SAO indirectly impacts the wave energy flux over spring and winter. All the in-situ wave height correlations showed changes when compared to partial correlations controlling for the other 2 modes. The SAO relationships showed the largest differences when accounting for the SAM and ENSO phases, generally reducing in strength. Constructive modal interference has led to both strong positive and negative anomalies in the past and will continue to do so in the future. The largest near-coast positive anomalies occurred under concurrent negative SAM and negative SAO, with more intense offshore anomalies under El Niño whereas the strongest negative anomalies occurred under a combination of La Niña with positive SAM and SAO phases.